The Legacy of J. Louis Martyn: Questions of Agency - Eastman, Susan Grove (Journal for the study of Paul and his letters, 2017)
Within an apocalyptic worldview characterized by an absolute division between divine and human agency, are human beings mere puppets in the larger drama of the cosmic conflict between God's liberating gospel and the powers of sin and death? Although this may seem to follow from some of the significant contributions made by J. Louis Martyn to the field of Pauline studies, it is a conclusion that Martyn himself consistently rejected. Thus, as we ponder the legacy of J. Louis Martyn in regard to matters of divine and human agency, we need to disentangle what is at stake in the relationship between the two, particularly in regard to the divine source of transforming power and the realm or arena in which this power is enacted.